Wybrane narzędzia Business Intelligence w obszarze finansów i rachunkowości - Leszczyńska, Maja; Łopaciński, Karol; Zygała, Ryszard (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Business Intelligence becomes part of the standard information technology set used by more and more businesses. To effectively manage the finance, managers need to analyze data collected from different sources and transform it into intelligence and knowledge. Business Intelligence tools сan significantly help managers in improving the basic financials functions. In this paper, the benefits and challenges of implementing BI in finance are discussed from different perspectives. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 322-338